Construction of Doctors' Criminal Liability in Handling Emergency Patients: Between Medical Negligence, Medical Risk, and First Aid Obligations - Rivan Picaso; Dwi Imroatus Sholikah; Burham Pranawa; Citra Cahyarini (Law Development Journal, 2026)
Emergency medical services are a form of healthcare that requires speed, accuracy, and professionalism from healthcare workers, particularly doctors. In practice, not all medical care leads to recovery, and in certain situations, it can result in disability or death. These conditions raise legal issues regarding the boundaries between medical negligence, medical risk, and the obligation to provide first aid in emergency situations. This study aims to analyze the construction of doctors' criminal liability in treating emergency patients based on Law Number 17 of 2023 concerning Health, the Indonesian Criminal Code, and health law doctrine in Indonesia. This study uses a normative juridical method with a statutory, conceptual, and case-based approach. The findings indicate that criminal liability for doctors in emergency services can only be imposed when an element of error in the form of gross negligence is proven, there is a causal relationship between the doctor's actions and the patient's harm, and there is no justification or excuse. The medical risks inherent in medical procedures cannot automatically be criminalized. On the other hand, doctors and healthcare facilities have a legal obligation to provide first aid to emergency patients without discrimination. This study emphasizes the need for a balanced legal formulation between patient protection and protection of the medical profession to avoid defensive medical practices in health services.